MENGENAL HURUF MELALUI MEDIA GRAFIS BERBASIS AUDIO VISUAL PADA ANAK KELOMPOK A1 RA MUSLIMAT NU 1 MALANG - Citra Mir Atur Rizqiyyah; Mohammad Afifulloh; Yorita Febry Lismanda (UNISMA, 2020)
Language development for early childhood is very important, which aims to enable the children to communicate well in their environment, basically his language development must go through several stages, the most basic is to recognize the letters. In recognizing letters not all children can recognize it well, from the results of research observations with Group A with 14 children in RA Muslimat NU 1 Malang as a research objects, it was found that they are difficult to recognize letters well because most teachers use the lecturing method in the learning process. The children feel bored with the monotonous learning process, it also makes the students show less enthusiastic in the learning process. The researcher uses an audio-visual graphics based media to introduce letters to children in the research process. The researcher used data collection techniques through observation, interviews, and documentation, with data analysis through data reduction, data display, drawing conclusion and verification. From the data collection, it can be seen that teaching using audio visual based graphics media can introduce letters to children well with a fun learning process.